Kualitas Fisik Rumah Dengan Kejadian Pneumonia Pada Balita - Tri Nindia; Imam Santoso; Juanda Juanda (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2019)
Abstrack : Physical Quality Density Of Houses With The Incedents Of Pneumonia In Children Under Five. Toddler pneumonia is an acute respiratory tract infection that is inflammation or irritation in one or both lungs, caused by infection. An illness is said to be acute if it has lasted ± 14 days. The purpose of this study was to determine the relationship of physical quality of houses (lighting, temperature, and humidity) and occupancy density with the incidence of pneumonia in children under five in Kecamatan Astambul, Kabupaten Banjar. Analytical research design with approach retrospective ( case control study ) in case comparison: control 1: 1. The sample of cases in this study were all houses of pneumonia patients 25 houses in the Astambul Health Center area in November 2018 - January 2019. Data analysis used chi-square test.The results of the research statistic showed that the lighting conditions (p 0.321>α 0.05) had no relationship, the temperature conditions (p 0.244 >α 0.05) had no relationship, and the condition of humidity (p 1.00>α 0.05) have no relationship with the incidence of pneumonia in infants.It is expected that counseling from Astambul public health center to society so they can increase knowledge and awareness about the requirements of a healthy home and pay attention to the health of their home environment.